2021
DOI: 10.1038/s41598-021-82310-4
|View full text |Cite|
|
Sign up to set email alerts
|

A novel methodology for epidemic risk assessment of COVID-19 outbreak

Abstract: We propose a novel data-driven framework for assessing the a-priori epidemic risk of a geographical area and for identifying high-risk areas within a country. Our risk index is evaluated as a function of three different components: the hazard of the disease, the exposure of the area and the vulnerability of its inhabitants. As an application, we discuss the case of COVID-19 outbreak in Italy. We characterize each of the twenty Italian regions by using available historical data on air pollution, human mobility,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 58 publications
3
72
0
1
Order By: Relevance
“…These results are more evident, for example, in Milan and Turin with an average seasonal PM 10 (PM 2.5 ) concentrations of about 30 (18) µg/m 3 (the higher of the panel), which had a positive correlation with daily COVID-19 cases ranging between 0.5 and 0.7, according to the Pearson's and Spearman's estimations. This long-term correlation effect, as discussed in the introduction, is consistent with different papers dealing with this topic [23,[29][30][31][32][33].…”
Section: Area Of Italy Citysupporting
confidence: 88%
See 1 more Smart Citation
“…These results are more evident, for example, in Milan and Turin with an average seasonal PM 10 (PM 2.5 ) concentrations of about 30 (18) µg/m 3 (the higher of the panel), which had a positive correlation with daily COVID-19 cases ranging between 0.5 and 0.7, according to the Pearson's and Spearman's estimations. This long-term correlation effect, as discussed in the introduction, is consistent with different papers dealing with this topic [23,[29][30][31][32][33].…”
Section: Area Of Italy Citysupporting
confidence: 88%
“…Overall, many studies have observed a direct correlation between long-term exposure to outdoor air pollution (e.g., high PM concentrations) with increased risk of respiratory disease [25][26][27][28]. This means that people living in areas with a higher pollution (longterm exposition) have developed a probably chronic inflammatory stimulus which may contribute to more COVID-19 cases and/or deaths [23,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The area with the largest number of infections and deaths in Italy is the Po Valley, which is also the foremost place of polluted air in Europe [111]. This result was first hypothesised [112] and later confirmed by another study [76] and a remarkable further one [99] that has controlled for five demographic co-variables. The fact that population density does not play a role in the incidence of COVID-19 in Italy and Iran is a result of our investigation that strongly supports the common hypotheses of these other studies and questions the widespread scepticism maintaining that air pollution usually overlaps with areas of high population density, and that the contribution of each to the virus incidence cannot be discerned (tested in Appendix B, Table A2).…”
Section: Discussionmentioning
confidence: 83%
“…However, such parameters are still under trials (Franklin et al., 2020). Hence, if the COVID‐19 risk assessment has to be performed, hazard and vulnerability parameters need to be defined (Pluchino et al., 2020). Providing sustainable threat protection from the COVID‐19 requires approaches that are proven in resisting the spread of this pandemic, mainly when it is a fact that it has no drug or vaccine to date (Rothan & Byrareddy, 2020).…”
Section: Introductionmentioning
confidence: 99%